Pelatihan Tepung Beras Fortifikasi Guna Menurunkan Kejadian Stunting di Desa Tebas Kabupaten Sambas - Fertiasari, Rini; Asta, Hidayat; Kristiandi, Kiki (Indonesia Berdaya, 2022)
Stunting is a health problem and threatens to improve the quality of an area. The SSGI 2021 stated that the stunting rate in Sambas reached 32.8%. The purpose of this community service is to conduct fortified rice flour training in helping to reduce the incidence of stunting. This product is the result of the milling process and the purpose of the product is to increase the value of micro and macronutrients and become an alternative food to help cases of stunting. The rice flour used in the manufacture of this flour is derived from local rice in the village of Tebas. This activity was carried out by women from Tebas Village with a total of 30 participants. The 30 participants were then regrouped into 5 teams so that the mothers in one team consisted of 6 participants. The result of these activities is that mothers are very enthusiastic because of these activities. in this activity, the mothers were taught to use drying equipment before going to flouring and the results of the rice flour were then processed derivatives that could be developed from the rice flour itself. Abstrak: Stunting merupakan permasalahan kesehatan dan mengancam terhadap peningkatan kualitas suatu wilayah. SSGI 2021 menyebutkan angka kejadian stunting di Sambas mencapai 32,8%. Tujuan dari pengbadian masyarakat ini adalah untuk melakukan pelatihan tepung beras fortifikasi dalam membantu menurunkan angka kejadian stunting. Produk ini merupakan hasil dari proses penggilingan dan tujuan dari produk tersebut adalah meningkatkan nilai zat gizi secara mikro dan makro dan menjadi salah satu pangan alternatif guna membantu kasus kejadian stunting. Tepug beras yang digunakan dalam pembuatan tepung ini merupakan berasal dari beras lokal yang ada di Desa Tebas. Kegiatan ini dilakukan oleh ibu-ibu yang berasal dari Desa Tebas dengan jumlah peserta sebanyak 30 peserta. Dari 30 peserta tersebut selanjutnya dikelompokan kembali jadi 5 tim sehingga ibu-ib Hasil dari kegiatan tersebut bahwa ibu-ibu sangat antusias karena dari kegiatan tersebut. dalam kegiatan ini ibu-ibu diajarkan dalam menggunakan alat pengeringan sebelum ke penepungan dan hasil dari tepung beras tersebut selanjutnya adalah turunan olahan yang dapat dikembangkan dari tepung beras itu sendiri.